Does Working From Home Affects Income ? Microdata Analysis Using Sakernas 2020 - Muhammad Kholisul Imam; Muhammad Salahudin Al Ayyubi; Anas Tania Januari (International Journal of Economics Development Research (IJEDR), 2023)
One of the measures taken by the government to stop the COVID-19 virus from spreading was to restrict community activities during the pandemic. The strategy is a shock to business movement and the work market. A pandemic has made financial specialists adjust to more readily dominant computerized innovation at work. They must be prepared to work from home. As a result, the primary objective of this research is to comprehend how employees' incomes are affected by working from home. The multinomial logit estimation technique was utilized in this investigation. The 2020 Indonesian National Labor Force Survey is the source of the statistics (SAKERNAS). Cross-sectional data on a number of factors, such as the economy, education, and a small set of demographics, are available in SAKERNAS. The findings indicate that businesses that allow employees to work from home typically experience a decline in income. More specifically, workers have yet to be able to maintain their household income levels thanks to the implementation of digitalization. According to this study, the increase in worker resilience during the pandemic was also influenced by socio-demographic factors: age, training experience, urban living, and educational attainment. The income loss brought on by the work-from-home strategy is closely related to the commercial sector. Several business sectors have different outcomes when work-from-home rules are implemented. The difference in impact is likely caused by a readiness to implement technology. With the goal that later on, it is important to increment computerized understanding and capability, particularly for areas encountering a decrease in pay.